Produk Esktraseluler Isolat Kapang Endofi t C.1.1 dan C.3.3 dari Ranting Cempaka Kuning (Michelia champaca L.) Sebagai Antimikroba - Adefira Elisyia Juniharti; Desi Nadya Aulena; Novi Yantih; Nur Miftahurrohmah; Shirly Kumala (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Michelia champaca L. is known to have effi cacy as an antimicrobial, antioxidant, and anticancer.In general, endophytic fungi that live in plant tissues is capable of producing secondary metabolites as theirhost plant. The objective of this research is to examine the antimicrobial potential of endophytic mold isolates C.1.1 and C.3.3 from yellow cempaka branches (Michelia champaca L.). Isolates obtained from previous research, fi rst was rejuvenated on PDA. Fermentation was carried out on each isolate for 12 days. The fermented supernatant was then extracted partially with n-hexane, ethyl acetate, and n-butanol solvent. The extract was then concentrated and tested for antimicrobial activity using disk diff usion and microdilution methods. N-butanol extract of endophytic fungi isolates of yellow champaca branches was able to inhibit the microbial growth with the largest inhibition area in isolate C.1.1 in Staphylococcus aureus ATCC 6538 (12.26 mm), Escherichia coli ATCC 8739 (11.40 mm), Candida albicans ATCC 10231 (10.50 mm), and Metichillin-Resistant Staphylococcus aureus (11.30 mm) with Minimum Inhibitory Concentration and Minimum Concentration of 12,5% . It was concluded that both endophytic fungi isolates of yellow champaca branches had the potential to inhibit the growth of pathogenic microbes.